2012
DOI: 10.1002/pc.22239
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and oxygen permeability of polyacrylonitrile/multiwalled carbon nanotubes composites

Abstract: Polyacrylonitrile (PAN)/Multiwalled carbon nanotube (MWCNT) nanocomposites were prepared by nonconventional ultrasonic‐assisted emulsifier free emulsion polymerization technique with variable percentage of functionalized carbon nanotube. PAN/MWCNT nanocomposites were characterized by ultraviolet‐visible (UV‐visible) spectroscopy and Fourier transform infrared (FTIR) spectroscopy. The result from UV‐visible suggested that the functionalized MWCNT had interfacial interaction with PAN matrices. The surface morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…This attempt-to-hop frequency, however, is a pre-factor that can be used to set the time scale. It was found that an attempt-to-hop frequency of ~10 4 s -1 leads to a time scale in reasonable agreement with experimental values in reference [92], so this value was used in this work for all simulations. The exponential in…”
Section: Charge Transportsupporting
confidence: 53%
See 2 more Smart Citations
“…This attempt-to-hop frequency, however, is a pre-factor that can be used to set the time scale. It was found that an attempt-to-hop frequency of ~10 4 s -1 leads to a time scale in reasonable agreement with experimental values in reference [92], so this value was used in this work for all simulations. The exponential in…”
Section: Charge Transportsupporting
confidence: 53%
“…(4) was chosen to be 0.6 Å -1 , which has been calculated for PAN [76]. Results from the simulations on box sizes of 800x100x100 (nm) 3 and 1000x100x100 (nm) 3 were fit to the power law and compared to experimental results on the conductivity of PAN/CNT composites ( Figure 12) taken from references [92,96]. These longer samples with NT aspect ratios of 1:400 were chosen for comparison because they were statistically indistinguishable from each other while also being the largest samples with maximum NT lengths, which are closer to the experimental reality, as previously discussed.…”
Section: Effect Of Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Polyacrylonitrile (PAN) is the main precursor for preparing the high strong carbon fiber, which has been used in aerospace, industrial and sports fields. The CNT/ PAN composite fibers by different spinning methods have excellent mechanical properties and electrical properties [4][5][6][7][8][9]. As we known, the structure of the nascent fibers obtaining by phase separation after the solidification bath plays an important role on the final properties of the PAN fibers, which have been studied by many researchers [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…polyacrylonitrile (PAN) is light weight, low cost, and easy processable polymer which can be used as a potential matrix for making of composite materials. In our previous work, we have synthesized various PAN nanocomposites by reinforcement of nanoclays , multiwalled carbon nanotube , graphite , and zirconium oxide nanopowder .…”
Section: Introductionmentioning
confidence: 99%